2014
DOI: 10.1074/jbc.m114.571414
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial RTX Toxins Allow Acute ATP Release from Human Erythrocytes Directly through the Toxin Pore

Abstract: Background: Hemolysis induced by the two RTX toxins HlyA and LtxA depends on ATP receptor activation. Results: HlyA and LtxA result in ATP release from human erythrocytes, which was unrelated to the main suggested ATP release pathway pannexin 1. Conclusion: ATP is released through a toxin pore. Significance: Adds new insights to the mechanism of these toxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 65 publications
1
52
0
Order By: Relevance
“…The authors show that bacterial pores too narrow to allow passage of ATP do not exhibit P2X receptor-dependent amplification of cell lysis (10). In support for this, we have shown that HlyA-induced ATP release is likely to occur directly through the HlyA-pore itself (11). This is exceedingly interesting because it implies that ATP will be released from any cell attacked by HlyA and thus, P2 receptors will be activated in an auto-and paracrine fashion directly subsequent to membrane insertion of HlyA.…”
supporting
confidence: 60%
“…The authors show that bacterial pores too narrow to allow passage of ATP do not exhibit P2X receptor-dependent amplification of cell lysis (10). In support for this, we have shown that HlyA-induced ATP release is likely to occur directly through the HlyA-pore itself (11). This is exceedingly interesting because it implies that ATP will be released from any cell attacked by HlyA and thus, P2 receptors will be activated in an auto-and paracrine fashion directly subsequent to membrane insertion of HlyA.…”
supporting
confidence: 60%
“…Recent findings indicated that E. coli HlyA and Aggregatibacter actinomycetemcomitans leukotoxin A induce ATP release from RBCs by forming toxin pores, which then acts on P2X1 and P2X7 to mediate hemolysis [27]. Therefore, we tested the role of ATP in ETX-induced hemolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Burnstock's early hypothesis that ATP, the major intracellular molecule providing the energy required for multiple biochemical and biophysical processes, may actually function as an extracellular non-adrenergic and noncholinergic signaling molecule [12,13] was received with great skepticism [14,15]. After several decades of extensive work, the scientific community came to the realization that ATP is widely employed as a signaling molecule in multiple biological processes in both normal and pathophysiological conditions [9,11,[16][17][18][19][20][21][22][23][24]. The rapid progress in understanding and deciphering multiple molecular mechanisms of signaling revealed that ATP is a potent mediator of multiple signaling cascades, which may act through binding to, and nonhydrolytic activation of, P2X ionotropic receptors or G Electronic supplementary material The online version of this article (doi:10.1007/s11302-016-9520-9) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple past studies focused on understanding the implications of ATP-controlled signaling with respect to endogenous transmembrane transporters such as ion channels [17,19,20,24,[28][29][30][31], there is a recent interest in understanding how ATP controls the lytic action of pore-forming toxins (PFTs) [22,26,27,[32][33][34]. PFTs introduce unregulated conducting pathways into the host cell plasmalemma [35][36][37][38][39], which is expected to yield direct cytolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation